1986
DOI: 10.1172/jci112666
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcemia may not be essential for the development of secondary hyperparathyroidism in chronic renal failure.

Abstract: Hypocalcemia is the main factor responsible for the genesis of secondary hyperparathyroidism in chronic renal disease. Studies with parathyroid cells obtained from uremic patients indicate that there is a shift in the set point for calcium-regulated hormone (parathyroid hormone [PIH) secretion. Studies were performed in dogs to further clarify this new potential mechanism. Hypocalcemia was prevented in uremic dogs by the administration of a high calcium diet. Initially, ionized calcium was 4.79±0.09 mg/dl and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(29 citation statements)
references
References 31 publications
(18 reference statements)
0
26
0
3
Order By: Relevance
“…The radioimmunoassay for PTH employed the antiserum CH9N which was developed in our laboratory. The characteristics ofthis amino-terminal assay have been described previously (17). Plasma levels of 1,25(OH)2D were measured by the method of Reinhardt et al (18).…”
Section: Methodsmentioning
confidence: 99%
“…The radioimmunoassay for PTH employed the antiserum CH9N which was developed in our laboratory. The characteristics ofthis amino-terminal assay have been described previously (17). Plasma levels of 1,25(OH)2D were measured by the method of Reinhardt et al (18).…”
Section: Methodsmentioning
confidence: 99%
“…All fragments show the loop region and the COOHterminal helix. His-14 to Leu-28 (loop and COOH-terminal helix) comprises the major part of the receptor binding region that is known to reside within His-14 to Phe-34 (5,6,68). The NH 2 -terminal helix, however, is present only in the in vivo bioactive fragments hPTH-(1-37) and hPTH-(2-37), but not in the inactive fragments hPTH-(3-37) and hPTH-(4 -37) (Table II).…”
Section: Structures Of Hpth Fragments 4312mentioning
confidence: 99%
“…In addition to the cyclic adenosine monophosphate (cAMP) pathway, involvement of the phosphatidylinositol hydrolysis signaling pathway is postulated for these functions (4). The receptor binding region mediating the calcium regulatory activity is located within sequence His-14 to Phe-34 (5,6). The complete NH 2 -terminal part of hPTH-(1-34) is required for stimulation of the cAMPdependent pathway (4), and the minimum sequence affecting bone and kidney comprises amino acids 2-27 (1,7).…”
mentioning
confidence: 99%
“…It is widely accepted that a decrease in serum calcium plays a role in the development of 2HPT. However, Lopez-Hilker et al [10] demonstrated that a decrease in calcium is not necessary, and that some other factors may be involved. Furthermore, increases in serum calcium in animals with 2HPT have been described before [11].…”
Section: Discussionmentioning
confidence: 99%